Synthesis and applications of magnetic nanoparticles for biorecognition and point of care medical diagnostics - Sandhu, Adarsh; Handa, Hiroshi; Abe, Masanori (Nanotechnology, 2010)
Functionalized magnetic nanoparticles are important components in biorecognition and medical diagnostics. Here, we present a review of our contribution to this interdisciplinary research field. We start by describing a simple one-step process for the synthesis of highly uniform ferrite nanoparticles ( d = 20–200 nm) and their functionalization with amino acids via carboxyl groups. For real-world applications, we used admicellar polymerization to produce 200 nm diameter ‘FG beads’, consisting of several 40 nm diameter ferrite nanoparticles encapsulated in a co-polymer of styrene and glycidyl methacrylate for high throughput molecular screening. The highly dispersive FG beads were functionalized with an ethylene glycol diglycidyl ether spacer and used for affinity purification of methotrexate—an anti-cancer agent. We synthesized sub-100 nm diameter magnetic nanocapsules by exploiting the self-assembly of viral capsid protein pentamers, where single 8, 20, and 27 nm nanoparticles were encapsulated with VP1 pentamers for applications including MRI contrast agents. The FG beads are now commercially available for use in fully automated bio-screening systems. We also incorporated europium complexes inside a polymer matrix to produce 140 nm diameter fluorescent-ferrite beads (FF beads), which emit at 618 nm. These FF beads were used for immunofluorescent staining for diagnosis of cancer metastases to lymph nodes during cancer resection surgery by labeling tumor cell epidermal growth factor receptor (EGFRs), and for the detection of brain natriuretic peptide (BNP)—a hormone secreted in excess amounts by the heart when stressed—to a level of 2.0 pg ml − 1 . We also describe our work on Hall biosensors made using InSb and GaAs/InGaAs/AlGaAs 2DEG heterostructures integrated with gold current strips to reduce measurement times. Our approach for the detection of sub-200 nm magnetic bead is also described: we exploit the magnetically induced capture of micrometer sized ‘probe beads’ by nanometer sized ‘target beads’, enabling the detection of small concentrations of beads as small as 8 nm in ‘pumpless’ microcapillary systems. Finally, we describe a ‘label-less homogeneous’ procedure referred to as ‘magneto-optical transmission (MT) sensing’, where the optical transmission of a solution containing rotating linear chains of magnetic nanobeads was used to detect biomolecules with pM-level sensitivity with a dynamic range of more than four orders of magnitude. Our research on the synthesis and applications of nanoparticles is particularly suitable for point of care diagnostics.